Plasmacytoma variant translocation 1 inhibits miR‐515‐5p function and modulates high mobility group B3 to promote the growth of prostate cancer cells. (11th September 2022) - Zhu, Xueying; Kang, Jian; Ma, Yupeng; Wang, Qi; Li, Weiwu; Su, Juan; Zhang, Xinqi
Abstract: Aim: This study is performed to analyze the role of long non‐coding RNA plasmacytoma variant translocation 1 in prostate cancer. Methods and materials: Plasmacytoma variant translocation 1, miR‐515‐5p, and high mobility group B3 mRNA expressions were examined using quantitative real‐time polymerase chain reaction and immunohistochemistry. After gain‐of‐function and loss‐of‐function models were established, the changes in cell proliferation, migration, and invasion were evaluated using cell counting kit‐8 assay, 5‐ethynyl‐2′‐deoxyuridine assay, and Transwell experiments. Validation of the targeting relationships between plasmacytoma variant translocation 1 and miR‐515‐5p, and between miR‐515‐5p and high mobility group B3 was conducted using bioinformatics prediction, a dual‐luciferase reporter assay, and an RNA immunoprecipitation experiment. Moreover, the effects of plasmacytoma variant translocation 1 and miR‐515‐5p on high mobility group B3 protein expression were examined using Western blot. Results: Plasmacytoma variant translocation 1 expression and high mobility group B3 expression were up‐regulated in prostate cancer tissues and cell lines while miR‐515‐5p expression was down‐regulated. Plasmacytoma variant translocation 1 knockdown restrained the proliferation, migration, and invasion of LNCaP and DU145 cells in vitro, and the transfection with miR‐515‐5p inhibitors reversed these effects. Mechanistically, plasmacytoma variant translocation 1 could repress the function of miR‐515; high mobility group B3 was proved to be a target gene of miR‐515‐5p, and its expression could be indirectly positively modulated by plasmacytoma variant translocation 1. Conclusion: Plasmacytoma variant translocation 1 accelerates prostate cancer progression by repressing miR‐515‐5p's function to upregulate high mobility group B3 expression.